2017
DOI: 10.1038/s41598-017-09022-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an anti-bacterial toxin by the biosynthetic enzyme CysK: mechanism of binding, interaction specificity and competition with cysteine synthase

Abstract: Contact-dependent growth inhibition (CDI) is a wide-spread mechanism of inter-bacterial competition. CDI+ bacteria deliver CdiA-CT toxins into neighboring bacteria and produce specific immunity proteins that protect against self-intoxication. The CdiA-CT toxin from uropathogenic Escherichia coli 536 is a latent tRNase that is only active when bound to the cysteine biosynthetic enzyme CysK. Remarkably, the CysK:CdiA-CT binding interaction mimics the ‘cysteine synthase’ complex of CysK:CysE. The C-terminal tails… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…The authors, in addition to the remarkable finding of a moonlighting function for CysK, proposed that the toxin forms a complex with CysK using the same structural motif used by CysE (i.e., insertion of the C-terminus in CysK active site). Further structural [70] and functional [24] studies confirmed the original finding and shed light on the details of complex formation and toxin activation. CysK/CdiA-CT complex is formed by two toxin monomers that bind to one CysK dimer with the C-terminal carboxylate engaging to the same binding site that is occupied by the substrate of the enzyme (Figure 2A).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The authors, in addition to the remarkable finding of a moonlighting function for CysK, proposed that the toxin forms a complex with CysK using the same structural motif used by CysE (i.e., insertion of the C-terminus in CysK active site). Further structural [70] and functional [24] studies confirmed the original finding and shed light on the details of complex formation and toxin activation. CysK/CdiA-CT complex is formed by two toxin monomers that bind to one CysK dimer with the C-terminal carboxylate engaging to the same binding site that is occupied by the substrate of the enzyme (Figure 2A).…”
Section: Introductionmentioning
confidence: 59%
“…Cysteine metabolism (i.e., de novo biosynthesis and degradation) [17], is intimately connected with many bacterial functions relevant to infection, such as resistance to oxidative stress and resistance to antibiotics [18,19,20,21,22], biofilm formation [23], and toxin activation [24,25]. For this reason, this metabolic pathway has received much attention in the last ten years as a potential target for the development of antibiotics or antibiotic enhancers [17,26,27,28,29,30,31,32,33,34,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…This hampers the accurate determination of the inhibition mechanism due to limitations to the range of inhibitor concentration that can be explored. However, since partial inhibition is a typical feature of allosteric inhibitors, we used a method developed by our group 24 to assess if compound 25 is able to displace a low affinity active site binder, 1-ethylcyclopropane-1,2-dicarboxylic acid, that forms a highly fluorescent complex with OASS. Compound 25 is unable to displace the compound up to an equimolar concentration of about 200 μM.…”
Section: Discussionmentioning
confidence: 99%
“…When the K d was lower than the concentration of the protein used in the assay, the dependence of the fluoresecnce emission intensity on ligand concentration was fitted to a quadratic equation that describes tight binding 23 . The fluorescence competitive binding assay, described elsewhere 24 , was used to evaluate whether compounds bind at the active site of the enzyme or to an allosteric site. The assay is based on the formation of a low-affinity, highly fluorescent complex between OASS and 1-ethylcyclopropane-1,2-dicarboxylic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of an immunity protein known as CdiI is responsible for the phenomenon (Aoki et al 2011). CdiI forms a complex with CdiA-CT to neutralize its tRNase activity but apparently this complex dissociates rapidly (Benoni et al 2017;Kaundal et al 2016). A study by Kaundal et al categorically demonstrates the role of CysK in stabilizing the binary complex CdiI/CdiA-CT with ~ 130 fold decrease in dissociation rate therefore, proving CysK to be a modulator of CdiA-CT/CdiI activity (Kaundal et al 2016;Johnson et al 2016).…”
Section: Role In CDImentioning
confidence: 99%